Family Empowerment Using Moringa Leaf Nuggets to Improve Dietary Adequacy Among Stunted Children: A Quasi-Experimental Study - Herlina Herlina; Titih Huriah (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Family empowerment through the utilization of local food resources is a strategic approach to improving dietary adequacy among children with stunting. Moringa leaves are nutrient-dense local foods that remain underutilized. This study aimed to examine the effect of family empowerment through the use of moringa leaf nuggets on energy intake adequacy among stunted children. This study employed a quasi-experimental pretest–posttest design with a control group. A total of 40 stunted children were assigned to an intervention group (n = 20) and a control group (n = 20). The intervention was conducted over three months and consisted of four empowerment stages (knowledge enhancement, self-efficacy strengthening, training, and evaluation), along with one month of moringa leaf nugget supplementation. The primary outcome was energy intake (kcal), assessed using food records and analyzed with dependent and independent t-tests. showed a significant increase in energy intake within the intervention group, from 886.13 ± 336.49 kcal at baseline to 1063.99 ± 208.04 kcal post-intervention (Δ = +177.86 kcal; p = 0.012). No significant change was observed in the control group (1117.69 ± 647.86 kcal to 1028.43 ± 251.53 kcal; p = 0.289). However, post-test comparison between the intervention and control groups revealed no statistically significant difference (1063.99 ± 208.04 vs. 1028.43 ± 251.53 kcal; p=0.324). Secondary outcomes demonstrated significant improvements in maternal knowledge and psychomotor skills, but not in attitudes. Family empowerment through moringa leaf nugget utilization significantly improved energy intake within the intervention group. However, the absence of a significant between-group difference suggests that the intervention’s effectiveness relative to the control remains inconclusive and warrants further investigation using larger samples and more rigorous designs Keywords: family empowerment, Moringa oleifera, Dietary intake, nutrient adequacy, child stunting, quasi-experimental study